Kinerja Unit PPA Satreskrim Polresta Kupang Kota dalam Menangani Kasus Tindak Pidana Kekerasan dalam Rumah Tangga (KDRT) - Nabila Aulia; I Putu Yoga Bumi Pradana; Aspri Budi Oktavianto (Universitas 17 Agustus 1945, 2025)
This study aims to analyze how the performance of the PPA Unit of the Kupang City Police Criminal Investigation Unit in handling cases of domestic violence that occur in Kupang City. The number of informants was 9 people. The performance theory used as the basis for analysis is the theory of Dwiyanto (2008), which includes four main indicators: Productivity, Responsiveness, Responsibilities. And Accountability. This research uses a qualitative approach with descriptive methods. Data was obtained through observation, interviews, documentation, and literature study. The data sources used are primary and secondary data. The triangulation technique used is source triangulation. The results showed that in terms of productivity, the PPA Unit of Kupang City Polresta needs to improve the quality of investigations, especially in collecting evidence and witnesses, the availability of inadequate RPK, good cooperation carried out by the PPA Unit of Kupang City Polresta with UPTD PPA Kupang City in handling domestic violence cases but there needs to be improvements in coordination procedures and the need for improvement in conducting socialization. In terms of responsiveness, the Kupang City Police PPA Unit showed concern and responded quickly to victim reports, but there were still obstacles in handling cases. In terms of responsiveness, the implementation of tasks is largely in accordance with applicable regulations, although there are technical errors in the implementation in the field. Meanwhile, in the indicator of